Influence of humidity on the decomposition process of double base rocket propellant - Romero Jabalquinto, Alonso; Mai, Nathalie; Mohammed, Yahaya; Gill, Philip P. (Elsevier, 2023)
The decomposition mechanisms of the polymer cellulose nitrate (NC) which is used in double base (DB) rocket propellants, have been extensively studied, and the influence of storage temperature on the lifetime of these energetic formulations is well known. However, the impact of humidity and water on the polymer decomposition process is poorly understood. This paper studies the influence of humidity on the decomposition chemistry of NC and its impact on shelf life. Stabiliser consumption was first analysed by ageing the propellant in sealed vials at different humidity levels for 7 days at an isothermal temperature of 90 °C. Samples were also analysed using heat flow calorimetry (HFC) at isothermal temperatures of 80 °C, 90 °C, and 100 °C. The results indicates that stabiliser depletion increases with increasing water content. Life assessment calculations (AOP 48 ed2) show that increasing the absolute humidity from 6 to 22 g m-3 will decrease the propellant life from 11 to 6 years (25 °C equivalents). The HFC results follow the same trend as the stabiliser depletion where greater absolute humidity increases the heat flow by up to 400 %. Unlike the pass/fail criteria for stabiliser depletion, the HFC samples passed the 10-year (25 °C equivalent) life criteria (STANAG 4582). A multi-temperature (80, 90, 100 °C) kinetic analysis of the initial heat flow showed that the heat flow rate increased with increasing humidity, but the activation energy for all humidity levels remained at 131 (± 3) kJ mol−1.
Keywords: Double base rocket propellant; Cellulose nitrate polymer decomposition process; Chemical stability; Heat flow calorimetry; Stabiliser consumption; Shelf life